(untitled) (Research, Society and Development, 2024)
Objective: To evaluate the treatment profile of supracondylar fractures of the pediatric humerus in a referral hospital in northeastern Brazil. Methodology: This is a retrospective observational study of data on patients who were treated at a pediatric urgent and emergency care referral unit of the Brazilian National Health System (SUS) between July 2022 and June 2023. Patients under the age of 13 diagnosed with a supracondylar humerus fracture were included in the study. Results: 197 patients were assessed, with a mean age of 5.4 years. Of these, 88 patients underwent surgery (44.6%), with a mean age of 5.3 years at the time of surgery and a predilection for males (54.5%). Of the patients who underwent surgery, 10 (11.5%) had to undergo open reduction to properly position the fracture. The main fixation pattern in the sample was fixation with crossed Kirschner wires (65.9%) and the majority of fixations were carried out using 2 Kirschner wires (76.5%). There was a statistically significant association between fracture severity (Gartland types III and IV) and open reduction. No type II cases had complications, while 3 type III and 2 type IV cases had complications. Conclusion: The data obtained is in line with the worldwide literature, except for the lower frequency of the general surgical approach and the higher frequency of cross-fixation in this study.